Effective diffusivity and activation energy in flours of residuals annatto grains - Santos, Dyego da Costa; Queiroz, Alexandre José de Melo; Figueirêdo, Rossana Maria Feitosa de; Oliveira, Emanuel Neto Alves de (Comunicata Scientiae, 2014)
The residual annatto grains are the subproduct from the extraction process of bixin, dye used infood, cosmetic and pharmaceutical industries. The most of this waste has been discarded in theenvironment, what constitutes wasteful since, like other grains, is source of carbohydrates, proteinand food fibers. One way to facilitate the use of these grains is suing them for making flour andincorporating them in commercial flour of other grains. This work aimed to determine the effectivediffusivity and obtain the activation energy in the drying process of flours of residuals annatto grains,with and without the oil layer from the process of industrial extraction of bixin. The dryings wasperformed at 40, 50, 60 and 70 °C, and air velocity of about 1 m s-1. The calculated value of theeffective diffusivity ranged from 0.23 × 10-11 to 2.24 × 10-11 m2 s-1 for the sample with oil, and 0.66 × 10-11 to 4.89 × 10-11 m2 s-1 for the sample without oil. The activation energies were of 70.56 and 58.95 KJmol-1 for the sample with oil and without oil, respectively, in which the samples without oil presentedhigher rates of drying.